2003
DOI: 10.1590/s0103-50532003000300018
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol robinobiosides and rutinosides from Alternanthera brasiliana (Amaranthaceae) and their effects on lymphocyte proliferation in vitro

Abstract: O extrato da espécie medicinal Alternanthera brasiliana Kuntze forneceu seis derivados die triglicosilados de kaempferol e quercetina. As estruturas foram elucidadas com base em RMN de 1 H e 13 C. Os seis flavonóides são inéditos no gênero. Kaempferol 3-O-robinobiosídeo e kaempferol 3-O-rutinosídeo inibiram mais eficientemente a proliferação de linfócitos humanos in vitro. The extract of the medicinal species Alternanthera brasiliana Kuntze afforded six di-and triglycosyl kaempferol and quercetin derivatives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
2
28
0
7
Order By: Relevance
“…This could be attributed to its higher total flavonoid content (69,034 mg/kg quercetin equivalent); higher flavonols (50,430 mg/kg quercetin equivalent) content compared to the total flavonoid (57,810 mg/kg quercetin equivalent) and total flavonols (8,710 mg/kg quercetin equivalent) of H. sabdariffa. Brachado et al (2003) identified six flavonoids in A. brasiliana leaf extract, out of which 3 inhibited lymphocyte proliferations. The high nitric oxide scavenging activity of the extracts suggests that the extracts be used in preventing inflammation, carcinomas and other diseases caused by nitric oxide radicals derived from cellular by-products as nitric oxide radical is known to play an important role in various inflammatory processes such as carcinomas, juvenile diabetes, multiple sclerosis, arthritis and ulcerative colitis (Hazra et al, 2008).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…This could be attributed to its higher total flavonoid content (69,034 mg/kg quercetin equivalent); higher flavonols (50,430 mg/kg quercetin equivalent) content compared to the total flavonoid (57,810 mg/kg quercetin equivalent) and total flavonols (8,710 mg/kg quercetin equivalent) of H. sabdariffa. Brachado et al (2003) identified six flavonoids in A. brasiliana leaf extract, out of which 3 inhibited lymphocyte proliferations. The high nitric oxide scavenging activity of the extracts suggests that the extracts be used in preventing inflammation, carcinomas and other diseases caused by nitric oxide radicals derived from cellular by-products as nitric oxide radical is known to play an important role in various inflammatory processes such as carcinomas, juvenile diabetes, multiple sclerosis, arthritis and ulcerative colitis (Hazra et al, 2008).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…The major A. tenella components that have been studied are tannins, saponins, flavonoid glycosides and heterosides, such as isorhamnetin, quercetin and kaempferol (Biella et al 2008), as well as other flavonoids, including vitexin and acacetin (Salvador et al 2006). Studies on the chemical composition of species of Alternanthera showed the presence of betalains, betacyanins, betaxanthins, chromo-alkaloids and flavonoids (Brochado et al 2003;Cai et al 2005;Salvador et al 2006). Betalains are N-heterocyclic natural pigments that are derived from the amino acid tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…The plant is used against inflammation, cough, and diarrhea in Brazilian popular medicine. [2] The extracts of A. brasiliana exhibited anti-nociceptive effects in mice, [3] antimicrobial effect, [4] and also anti-herpes simplex virus activity. [5] Aqueous or ethanolic extracts of A. brasiliana are able to block human mitogeninduced lymphocyte proliferation without any toxic effect.…”
Section: Introductionmentioning
confidence: 99%